'Nothing is Certain': Czech Post-War Literature Between the Avant-Garde and Expressionism. (2nd July 2016) - Říhová, Zuzana
Abstract : The Czech post-war avant-garde is split between collective enthusiasm, the adoration of the masses, and the depiction of the lone individual in crisis. Interpretations of this period have until now been based on the opposition of Literární skupina (the 'Literary Group', with an expressionist, individualist platform) vs. Devětsil (with an avant-gardist, collectivist platform). This study examines how understanding of the terms 'expressionist' and 'avant-garde' changed in the period in which Literární skupina and Devětsil emerged, followed by literary historical reflections on this process during the 1960s and 1970s, when Literární skupina came to be seen as distinct from the avant-garde on the basis of its espousal of expressionism. By comparing theoretical discourse and literary texts — in particular, hitherto overlooked avant-garde short prose — the present article examines the extent to which these established oppositions are valid. This article argues that expanding the analysis to include the neglected genre of the short story brings greater nuance to the underlying opposition of 'expressionism vs. avant-garde' (and individualism vs. collectivism), and thereby challenges standard interpretations of the era in question.